Pengaruh Pendidikan Dan Pengangguran Terhadap Kemiskinan Di Kota Probolinggo, Kabupaten Probolinggo, Kabupaten Lumajang - Hanun, Imas Cik; prabowo, prayudi setiawan (Independent: Journal of Economics, 2022)
The purpose this research is to find out how influential education and unemployment are on proverty in Probolinggo Regency, Probolinggo City and Lumajang Regency, using a quantitative associative approach with a research period of 11 (eleven) years, form 2010 to 2020. The data used are secondary data using a panel analysis tool, composed of cross-sectional data form 3 Regencies/Cities in East Java and time series data for the periode 2010-2020. The results show that proverty in probolinggo City, Probolinggo Regency and lumajang Regency can be explained by education and unemployment of 82%. Education and unemployment simultaneously have an influence on proverty with a probability value of 0.000000. Partially education with indicators of high school graduates > 15 years has no effect on proverty, has a probability of 0.4811, while unemployment with an indicator of poor people not working > 15 years has an influence on proverty, the probability is 0.0017.